[Письма, 1856-1862 - Толстой Лев Николаевич (1992)
Вых. дан. ориг.: М.: Гослитиздат, 1949. Экземпляры: КХ (20111015) / Инвентарный номер: 1010497 / Сис.шифр: Р1 / Авт.знак: Т 53 / ГРНТИ: 17 / ББК: 84(2=411.2)-4